Working towards the Monarchy : The Politics of Space in Downtown Bangkok - Ünaldi, Serhat (Book collections on Project MUSE., 2016)
In the twilight years of Thailand's ailing King Bhumibol, battles between royalists and their red shirt opponents are increasing, and the tectonic shifts that lie beneath Thailand's decade-old political crisis have become increasingly apparent. Serhat Ünaldi sheds new light on recent developments with its bold analysis of urban space in downtown Bangkok.